Trimetazidine effects on red blood cell membrane lipids and necrosis area size in thrombolytic therapy of myocardial infarction - T. Yu. Rebrova; S. A. Afanasyev; V. A. Perchatkin; I. V. Maksimov; V. A. Markov (Кардиоваскулярная терапия и профилактика, 2009)
Aim. То assess the effects of an anti-ischemic medication trimetazidine on necrosis area size, lipid peroxidation (LPO) and membrane phosphohpids in thrombolytic therapy (ТLТ) of acute myocardial infarction (AMI).Material and methods. The study included 79 AMI patients. Coronary artery recanalisation was achieved by intravenous bolus administration of streptase (750 000 Units). All patients received anticoagulants, disaggregants, beta-adrenoblockers, nitrates, and ACE inhibitors, according to the relevant indications and contraindications. The control group (CG) included 39 patients. Before TLT the main group (MG; n=40) was administered trimetazidine 40 mg/kg per os, followed by the dose of 60 mg/day. Myocardial ischemia severity was assessed by QRS-index and total creatine phosphokinase activity (CK) in plasma. LPO activity was assessed by serum levels of malonic dialdehyde (MDA). PhosphoUpid (PHL) profile of ted blood cell membranes was measured by thin layer chromatography method.Results. Trimetazidine administration (60 pg/day per os) in reperfusion period was associated with significant decrease in anginal attack number, daily nitrate dose, reperfusion myocardial damage severity, and serum MDA concentration, comparing to the controls. In red blood cell membranes, concentrations of phosphatidyl chohne, phosphatidyl serine and sphingomyelin were significantly higher in the MG than in the CG, which points to trimetazidine impact on these metabolites in myocardial reperfusion. Simultaneous reduction in phosphatidyl ethanolamine level could be due to its involvement in phosphatidyl choline and phosphatidyl serine synthesis, stimulated by trimetazidine.Conclusion. Trimetazidine therapy in AMI patients increased TLT effectiveness, due to reduced LPO and cell membrane PL normalization, improved myocardiocyte viability and beneficial effects on post-MI myocardial remodeling.